Vinculación entre los estilos de aprendizaje y enseñanza para el logro de un aprendizaje significativo - Huanca Hancco, Ana Lizbeth (2016)
The present article aims to evaluate some theoretical fundamentals and a brief bibliography review about some conceptualizations of the Teaching and Learning Styles constructs in the last decades, the close link among both variables has the purpose of generating a self-reflection in the teachers about their own pedagogical practices based on the theory of different individuals so as to guarantee a quality teaching and a significant learning. Furthermore, a first teacher's task will be to identify which of the four styles of learning predominates in his class group, to adapt his own style of teaching according to the students learning styles, giving them the tools and strategies for the achievement of the educational objectives, thus avoiding educational failure.